Arthur's underwear - Brown, Marc (Boston, Mass. : Little, Brown, 2000)
It takes a really embarrassing moment in the school cafeteria to cure Arthur of his fear of being caught in his underwear.
"An Arthur adventure."
G1
Keywords: Aardvark -- Fiction; Embarrassment -- Fiction; Schools -- Fiction